2004
DOI: 10.1074/jbc.m408733200
|View full text |Cite
|
Sign up to set email alerts
|

The Epstein-Barr Virus Polymerase Accessory Factor BMRF1 Adopts a Ring-shaped Structure as Visualized by Electron Microscopy

Abstract: Epstein-Barr virus (EBV) encodes a set of core replication factors used during lytic infection in human cellsthat parallels the factors used in many other systems. These include a DNA polymerase and its accessory factor, a helicase/primase, and a single strand binding protein. The EBV polymerase accessory factor has been identified as the product of the BMRF1 gene and has been shown by functional assays to increase the activity and processivity of the polymerase. Unlike other members of this class of factors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
(16 reference statements)
2
7
0
Order By: Relevance
“…Although BMRF1 also possesses DNA binding activity (18), its stoichiometry for DNA binding remains unknown. Electron microscopy observations revealed that BMRF1 adopts a ring-shaped structure, which may contain six monomers (19). This is almost twice as large as the previously reported PCNA ring structure.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…Although BMRF1 also possesses DNA binding activity (18), its stoichiometry for DNA binding remains unknown. Electron microscopy observations revealed that BMRF1 adopts a ring-shaped structure, which may contain six monomers (19). This is almost twice as large as the previously reported PCNA ring structure.…”
supporting
confidence: 62%
“…According to an electron microscopy study (19), a ring structure with a 55-Å diameter was observed for intact BMRF1, which includes six molecules within the ring. The crystal structure of BMRF1-WT⌬C showed an elliptic ring (long axis ϳ50 Å, short axis ϳ40 Å).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent electron microscopy study indicated that the UL44 homolog from the ␥-herpesvirus Epstein-Barr virus assembles in a higher ordered structure that is reminiscent of a lock washer or ring-like arrangement (60). Furthermore, the inner diameter of the rings in these electron microscope images have widths similar to that of the central cavity of the infinite "lock washer" helical arrangement of dimers observed in the UL44-UL54 crystal lattice.…”
Section: Ul44 May Be Capable Of Forming Highermentioning
confidence: 65%
“…Although the side chain of Ile 135 forms some van der Waals interactions with the peptide, including the sulfur of Cys 1241 and C-␤ of Ala 1238 , these interactions are less extensive than the hydrophobic interactions that Ile 135 makes with other side chains of UL44. Thus, the side chain of Ile 135 is positioned as a hydrophobic "anchor" underneath the hydrogen-bonding network, where it makes favorable van der Waals contacts with several important residues from the central ␤-sheet of UL44, including Val 41 , Ile 49 , and the aliphatic portions of Gln 51 and Lys 60 . The second set of interactions involves the packing of a hydrophobic "plug" into a crevice along the central ␤-sheet of UL44 (Fig.…”
Section: Resultsmentioning
confidence: 99%